1, 16‐Di‐tert‐butyl‐1, 16‐diphospha[5.5]ferrocenophane: Synthesis, Reactions and Mössbauer Spectroscopy. Issue 46 (10th December 2018) - Werner, Irina; Heinisch, Sandra Lauren; Nowik, Israel; Herber, Rolfe H.; Butenschön, Holger
Abstract: 1, 16‐Di‐ tert ‐butyl‐1, 16‐diphospha[5.5]ferrocenophane was prepared in 76% yield by deprotonation of 1, 1'‐di(2‐ tert ‐butylphosphanylethyl)ferrocene followed by treatment with 1, 1'‐di(2‐bromoethyl)ferrocene. The ferrocenophane exists as a mixture of syn and anti diastereomers, which were separated by repeated precipitation of one of them. Reaction with borane afforded the respective borane adducts in 47% yield. Methylation with iodomethane gave the respective diphosphonium salt in quantitative yield. Oxidation with 1.0 or 5.0 equivalents of silver hexafloroantimonate gave a green and a blue material, respectively, presumably the mono and the diferrcenium salts. 1, 16‐Di‐ tert ‐butyl‐1, 16‐diphospha[5.5]ferrocenophane and its oxidation products were subjected to a temperature‐dependent Mössbauer effect (ME) study to elucidate their dynamical and paramagnetic relaxation characteristics. The ME data are consistent with the absence of spin averaging for the two distinct Fe sites in the monooxidation product over the temperature range 91< T <236 K. The metal atom vibrational amplitudes as a function of temperature have been determined for 1, 16‐di‐ tert ‐butyl‐1, 16‐diphospha[5.5]ferrocenophane as well as for the diamagnetic site in the monooxidation product. Abstract : The title compound was prepared as the first diphospha[5.5]ferrocenophane from 1, 1'‐di(2‐ tert ‐butylphosphanylethyl)ferrocene by double deprotonation by treatment with 1, 1'‐di(2‐bromoethyl)ferrocene. The compound exists as syn and anti diastereomers. In addition to borylation and methylation reactions, oxidation experiments as well as an extensive Mössbauer study are reported.